Two new species of Megarthrus (Coleoptera, Staphylinidae, Proteininae) from Mexican Cloud Forests - Rodríguez, William David; Navarrete-Heredia, José L.; Arriaga-Varela, Emmanuel; Cuccodoro, Giulio (Zootaxa, 2020)
Two new species of Megarthrus are described from cloud forests of the Mexican state of Veracruz: M. cavianae Rodríguez, Navarrete-Heredia & Arriaga-Varela sp. nov., and Chiapas: M. chiapas Cuccodoro sp. nov. They differ from the two hitherto known Mexican species M. altivagans Bernhauer, 1929, and M. alatorreorum Rodríguez & Navarrete-Heredia, 2015, both from temperate forests of the Transmexican Volcanic Belt, by having synapomorphic features of the M. inaequalis-supergroup of species. This lineage includes all the Central and South American members of the genus, with the inclusion of these species, the distribution of the group is extend by more than 5 degree of latitude to the North. Within this lineage, the two new species share a very peculiar morphology of the male abdominal sternite VIII found elsewhere in the genus only in M. flavosignatus Bierig, 1940, and M. zunilensis Sharp, 1887, with which they form the M. zunilensis-group of species defined here.